THE EFFECT OF Ge CONTENT ON THE OPTICAL AND ELECTRICAL PROPERTIES OF a-SiGe:H THIN FILMS - Mursal Mursal; Irhamni Irhamni; Toto Winata (Universitas Syiah Kuala, 2013)
The effect of Ge content on the optical and electrical properties of Si-Ge-H thin films deposited by HWCPECVDhad been investigated. The Si- Ge-H films ware grown on corning glass 7059 substrate using 10% dilutedGeH4 and SiH4 gas mixture, respectively. The GeH4 gas flow rate was varied from 2.5 to 12.5 sccm, while the flowrate of SiH was kept constant at 70 sccm. The results showed that the deposition rate of Si-Ge-H thin films wasincreases with the increasing of GeH4 gas flow rate. Beside, the Ge content in the film also increased, and the opticalband gap decreased. The dark conductivity of Si- Ge-H films was relatively constant, whereas the photo ’sconductivity decreased with increasing of Ge content.